2017
DOI: 10.1590/0103-8478cr20160618
|View full text |Cite
|
Sign up to set email alerts
|

A time series analysis of bulk tank somatic cell counts of dairy herds located in Brazil and the United States

Abstract: Bulk tank somatic cell counts (BTSCC) is widely used to monitore the mammary gland health at the herd and regional level. The BTSCC time series from specific regions or countries can be used to compare the mammary gland health and estimate the trend of subclinical mastitis at the regional level. Three time series of BTSCC from dairy herds located in the USA and the Southeastern Brazil were evaluated from 1995 to 2014. Descriptive statistics and a linear regression model were used to evaluate the data of the BT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…Findings of the present study showed that 50% of the herds presented BMSCC ≥400,000 cell/mL, with mean of 483,000 cell/mL. These results are in agreement with those reported by Rodrigues et al (2017), who verified a geometric annual BMSCC mean in herds in southeastern Brazil of 518,000 cell/mL, with a confidence interval from 491,000 to 546,000 cell/mL; these results are similar to those found in the present study -483,000 cell/mL. High levels of BMSCC can cause numerous losses to the dairy industry, because they directly affect the composition of milk and, consequently, reduce its shelf life and that of its derivatives (Silva & Nogueira 2010).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Findings of the present study showed that 50% of the herds presented BMSCC ≥400,000 cell/mL, with mean of 483,000 cell/mL. These results are in agreement with those reported by Rodrigues et al (2017), who verified a geometric annual BMSCC mean in herds in southeastern Brazil of 518,000 cell/mL, with a confidence interval from 491,000 to 546,000 cell/mL; these results are similar to those found in the present study -483,000 cell/mL. High levels of BMSCC can cause numerous losses to the dairy industry, because they directly affect the composition of milk and, consequently, reduce its shelf life and that of its derivatives (Silva & Nogueira 2010).…”
Section: Resultssupporting
confidence: 93%
“…The high prevalence rates observed in the present survey for pathogens S. aureus and S. agalactiae (Table 1) suggest that the control measures for infectious mastitis are not being correctly applied, a finding that corroborates the results reported by Rodrigues et al (2017). This fact emphasizes the need to adopt specific measures for the control of these contagious pathogens that affect the daily production of herds and the milk quality, especially the BMSCC index.…”
Section: Resultssupporting
confidence: 82%
“…Bulk tank SCC worldwide SCC measured at bulk tank level is a widely used indicator when troubleshooting herds with multiple milk quality and allows an estimate of the trends of clinical and subclinical mastitis at the herd and regional level (Olde Riekerink et al, 2007;Rodrigues et al, 2017). Moreover, bulk tank SCC is significantly correlated with polymorphonuclear neutrophilic leukocytes (PMN) content of milk, which is influenced by environmental temperature and act as a vital indicator of dairy herd health (O'Sullivan et al, 1992;Kelly et al, 2000).…”
Section: Heat Stress and Somatic Cell Count (Scc)mentioning
confidence: 99%
“…agalactiae (see Table 1) indicates that control measures for contagious mastitis have not been applied correctly. This points to a need for specific measures to control these contagious pathogens that impact the productivity of herds and the quality of milk, especially when it comes to the BMSCC (RODRIGUES et al, 2017).…”
Section: Resultsmentioning
confidence: 99%